2020
DOI: 10.3390/su12156011
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Analysis for the Categorization of the Negative Externalities of Transport and the Hierarchical Organization of Sustainable Mobility’s Strategies

Abstract: Transport systems are capable of contributing to the economic robustness of a geographic area and the well-being of its inhabitants via the supply of the necessary assets for the mobility of people and goods. However, transport projects have the capacity to produce several negative externalities such as water pollution, air pollution, barrier effects, noise, and ecological impact, which affect the quality of people’s life. Considering these facts, the main purpose of this study is to indicate methodologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 56 publications
0
21
0
1
Order By: Relevance
“…The third aspect was focused on road accidents and air pollution, two of the main negative externalities that result from the greater use of individual transport and longer distances, which was reinforced by the inability of public transport in peripheral municipalities. These negative externalities contributing to the negative sense of a livable urban organization at all levels [8,68,69]. Although pedestrians and cyclists are the most sensitive elements in the global context of the transport system, studies have verified benefits in the modal shift from motorized to active transport, with more benefits than risks for all users [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…The third aspect was focused on road accidents and air pollution, two of the main negative externalities that result from the greater use of individual transport and longer distances, which was reinforced by the inability of public transport in peripheral municipalities. These negative externalities contributing to the negative sense of a livable urban organization at all levels [8,68,69]. Although pedestrians and cyclists are the most sensitive elements in the global context of the transport system, studies have verified benefits in the modal shift from motorized to active transport, with more benefits than risks for all users [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified private car ownership as main cause of negative externalities. Problems of high transport energy usage [87] along with issues of traffic congestion, noise, road damage, and the invasion of public space [88] have proved a challenge to progressing towards environmental sustainability. Additionally, studies on mobility in the urban area of Brussels and regions beyond [89,90] have stressed the need for removing the dominant use of the individual car, in order to reduce social costs in terms of air pollution, noise, accidents, and congestion.…”
Section: Discussionmentioning
confidence: 99%
“…Limited land and budget resources, growing traffic demand, and congestion make city transport planning crucial to enable accessibility, quality of life, and economic growth. This is a challenging task as not only do private vehicles have many negative externalities [1], but today's planning and evaluation tools are biased toward investments in roads [2]. This paper develops and suggests a new urban transit investment model toward optimizing investments in public transport, the fundamental motorized sustainable transportation mode which enables more walkable and sustainable cities.…”
Section: Introductionmentioning
confidence: 99%